Keadilan Transaksional dalam E-Commerce Halal: Tinjauan Ekonomi Syariah - A. Rahman; Feri Sofiyan; Zuhrah Zuhrah (IAIN Langsa, 2026)
This study aims to examine the concept of transactional justice in halal e-commerce from the perspective of Islamic economic law and to reconstruct the principles of digital transactions in line with the objectives of Maqāṣid al-Sharī‘ah. This research employs a qualitative library research design using a normative juridical approach through conceptual and statutory approaches. Primary sources consist of the Qur'an, Hadith, Fatwas of the Indonesian National Sharia Council (DSN-MUI), and regulations governing electronic commerce, while secondary sources include Scopus-indexed journal articles, scholarly books, and relevant literature on Islamic economic law. Data were analyzed using descriptive-analytical methods supported by content analysis. The findings reveal that transactional justice in halal e-commerce extends beyond the halal status of products and requires fairness throughout the entire digital transaction process. This includes reconstructing digital contracts to prevent gharar through information transparency and algorithmic accountability, strengthening consumer protection by implementing digital khiyār as a corrective mechanism against information asymmetry, and promoting distributive justice through platform governance that supports fair competition and empowers micro, small, and medium enterprises (MSMEs). This study contributes by proposing transactional justice as an integrative framework that connects digital contractual principles, consumer protection, and distributive justice, thereby enriching the discourse on Islamic economic law and providing a normative foundation for the development of a fair and sustainable halal e-commerce ecosystem